First Report of Metarhizium viridulum Isolated from the Cicada (Cryptotympana atrata) in South Korea - Seung-Yoon Oh; Yunhyeok Jang (한국균학회지)
Metarhizium, a genus of entomopathogenic fungi distributed globally, infects a wide range of insect hosts. To date, five species have been documented in South Korea. During a survey of cicada (Cryptotympana atrata)-associated fungal diversity, we discovered an unexpected case of fungal infection. Morphological examination and molecular phylogenetic analysis identified the isolated fungal strain as Metarhizium viridulum, a species not previously reported in South Korea. This study presents the detailed morphological characteristics and phylogenetic position of the isolated M. viridulum strain, expanding our understanding of Metarhizium diversity in South Korea.